Synergistic air pollution exposure elevates depression risk: a cohort study - Hao, Yuqing; Xu, Longzhu; Peng, Meiyu; Yang, Zhugen; Wang, Weiqi; Meng, Fanyu (Elsevier, 2025)
Depression is a leading mental health disorder worldwide, contributing substantially to the global disease burden. While emerging evidence suggests links between specific air pollutants and depression, the potential interactions among multiple pollutants remain underexplored. Here we show the influence of six common air pollutants on depressive symptoms among middle-aged and older Chinese adults. In single-pollutant models, a 10 μg m−3 increase in SO2, CO, PM10, and PM2.5 is associated with increased risks of depressive symptoms, with odds ratios (95% confidence intervals) of 1.276 (1.238–1.315), 1.007 (1.006–1.008), 1.066 (1.055–1.078), and 1.130 (1.108–1.153), respectively. In two-pollutant models, SO2 remains significantly associated with depressive symptoms after adjusting for other pollutants. Multi-pollutant models uncover synergistic effects, with SO2, CO, NO2, PM10, and PM2.5 exhibiting significant interactions, identifying SO2 as the primary driver of these associations. Mediation analyses further indicate that cognitive and physical impairments partially mediate the relationship between air pollution and depressive symptoms. These findings underscore the critical mental health impacts of air pollution and highlight the need for integrated air quality management strategies. Targeted mitigation of specific pollutants, particularly SO2, is expected to significantly enhance public mental health outcomes.
Keywords: 41 Environmental Sciences; 4105 Pollution and Contamination; Clinical Research; Behavioral and Social Science; Climate-Related Exposures and Conditions; Mental Illness; Mental Health; Social Determinants of Health; Brain Disorders; Depression; 2.2 Factors relating to the physical environment; 3 Good Health and Well Being; 4011 Environmental engineering; 4103 Environmental biotechnology; 4104 Environmental management; Air pollution; Long-term exposure; Depressive symptoms; Joint effect; Mediation analysis